Medicare' Hospital-Acquired Condition Reduction Program and Community Diversity in the United States: The Need to Account for Racial and Ethnic Segregation. Issue 4 (2nd October 2019) - Hamadi, Hanadi; Tafili, Aurora; Apatu, Emma; Park, Sinyoung; Spaulding, Aaron
Abstract: This study investigated the association between community diversity within hospitals' referral region (HRR) and hospital-acquired conditions (HACs) incident rate among adults ages ≥ 65 years. HRR level ( n  = 274) HACs were examined and the analysis showed that high diverse communities (OR 1.48, 95% CI [1.15, 1.91]) had higher adjusted odds than low diverse communities to score poorly on Domain 2, and increased odds of scoring poor on overall total HAC score. Although hospital quality of care is not intentionally segregated, its surrounding community is impacting its performance, thus policymakers need to accommodate the diversity of communities when developing pay-for-performance or merit-based initiatives.